2013
DOI: 10.1007/s11011-013-9432-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of PAH gene in patients with PKU in western Iran and its association with polymorphisms: identification of four novel mutations

Abstract: Phenylketonuria (PKU) is an autosomal recessive disorder characterized by a mutation in the phenylalanine hydroxylase (PAH) gene. Untreated PKU can lead to mental retardation, seizures, and other serious medical problems. This study was designed to investigate the status of molecular defects in the PAH gene and their association with polymorphisms in Kurdish patients with PKU in the Kermanshah province, western Iran. The study was conducted on 27 unrelated patients with PKU over a 2-year period (from 2010 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…North China (%) [6] South China (%) [15] Taiwan (%) [8] Korea (%) [15] Czech (%) [16] Lithuania (%) [16] Brazil (%) [ [9,20]. Although the exact reason behind the specific PAH mutation pattern in this area and in Northern and Western regions of China remains unclear, investigation on PAH mutation spectrum of north Jiangsu can facilitate the diagnosis and prognosis of PKU patients in this region.…”
Section: Mutations North Jiangsu (%)mentioning
confidence: 99%
“…North China (%) [6] South China (%) [15] Taiwan (%) [8] Korea (%) [15] Czech (%) [16] Lithuania (%) [16] Brazil (%) [ [9,20]. Although the exact reason behind the specific PAH mutation pattern in this area and in Northern and Western regions of China remains unclear, investigation on PAH mutation spectrum of north Jiangsu can facilitate the diagnosis and prognosis of PKU patients in this region.…”
Section: Mutations North Jiangsu (%)mentioning
confidence: 99%
“…Fifteen different mutations were observed on molecular analysis of PAH gene in 51 of the 54 alleles in Kurdish PKU patients in West of Iran. [ 8 ] The c.168 + 5G>C mutation was the most prevalent mutation with the frequency of 26%. In Kermanshah province – located at West of Iran with mainly Kurd population-p. R261Q was observed just in one chromosome of 25 PKU patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 In the southwest of Iran and the Khuzestan Province, molecular analysis confirmed detection of thirteen different mutations affecting the PAH gene which was anticipated due to the ethnic heterogeneity of the specified region. 36 In western Iran, Alibakhshi and co-workers confirmed a distinct difference existing concerning the characteristics of PAH mutations between the Kermanshah province and other areas of Iran. It has been suggested that Kermanshah, also known as the gateway to Asia, may have a unique population distribution of PAH gene mutations as it lies and 2016 versus 2017 (p<0.001).…”
Section: Concerningmentioning
confidence: 94%